The Influence of Green Corporate Social Responsibility on Firm Value with the Audit Committee as a Moderating Variable - Andre Pratama; Ruhul Fitrios (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
This research aims to prove and analyze the impact of green corporate social responsibility (CSR) on company value and the role of the audit committee as a moderating variable. The population is all corporates exist on the Indonesian Stock Exchange (IDX) during 2015-2019. The study used purposeful sampling and obtained as many as 125 companies. The analysis methods used are simple linear analysis and moderate regression analysis. Finding research show that green CSR affects corporate value, and the audit committee can ease correlate between green corporate social responsibility and corporate value.